Chuan Huang Fang combining reduced glutathione in treating acute kidney injury (grades 1–2) on chronic kidney disease (stages 2–4): A multicenter randomized controlled clinical trial - Chen, Ling; Ye, Zi; Wang, Danjun; Liu, Jianlian; Wang, Qian; Wang, Chen; Xu, Bing; Gong, Xuezhong (Frontiers in Pharmacology, 2022)
Lack of effective drugs for acute kidney injury (AKI) grades 1–2 is a crucial challenge in clinic. Our previously single-center clinical studies indicated Chuan Huang Fang (CHF) might have nephroprotection in AKI on chronic kidney disease (CKD) (A on C) patients by preventing oxidant damage and inhibiting inflammation. Reduced glutathione (RG) has recently been shown to increase the clinical effectiveness of high-flux hemodialysis among patients with severe AKI. In this multicenter randomized controlled clinical study, we designed a new protocol to assess the efficacy and safety of CHF combining RG in patients with A on C. We also explored therapeutic mechanisms from renal fibrosis biomarkers. 98 participants were randomly and equally divided into the RG and RG+CHF subgroups. The RG and RG+CHF groups received general treatments with RG and a combination of RG and CHF, respectively. The therapy lasted for two weeks. In this study, the primary assessment result was a difference in the slope of serum creatinine (Scr) over the course of two weeks. The secondary evaluation outcomes were alterations in blood urea nitrogen (BUN), uric acid (UA), estimated glomerular filtration rate (eGFR), urinary AKI biomarkers, renal fibrosis biomarkers (transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF)), and traditional Chinese medicine (TCM) symptoms. Furthermore, vital signs and adverse events (AEs) were observed. Both groups had a slower renal function decline after treatment than before treatment. Compared with RG group, more reductions of Scr, BUN, UA, and better improvement of eGFR were observed in RG+CHF group (p < 0.05). Additionally, the levels of urinary AKI biomarkers, renal fibrosis biomarkers, and TCM syndromes were decreased in RG+CHF group versus RG group (p < 0.05). No significant between-group differences were observed of AEs. We thus concluded this novel therapy of CHF combining RG might be a useful method for treating A on C patients.